Looking at law through children's eyes - Hopman, Marieke J. (Cambridge : Intersentia, 2021)
Since the adoption of the 1989 UN Convention on the Rights of the Child, all children in the world have rights that are protected by states - at least in theory. In practice, children's rights are grossly violated on a daily basis and on a global scale. Studies in children's rights struggle to find why this is the case, and what can be possibly done to change this situation. This publication proposes that a better understanding of children's rights violations may be achieved if looking at law from a child's perspective. This means that a researcher has to go beyond the analysis of international conventions and national law, to include what is perceived as law by children. This book presents a new theoretical framework and methodology for finding law for children, combining legal pluralism, law and sociology, philosophy of law and legal empirical research. This framework is then put to the test in three case studies, all which include empirical research data. The book explores the possible legal orders that arise when looking at law through children's eyes, such as the household and the classroom. These legal orders, that we find when looking at law through children's eyes, have to be recognized as part of a complete picture of law influencing the protection and/or violation of children's rights.
Title from publisher's bibliographic system (viewed on 28 May 2021).
Keywords: Children -- Legal status, laws, etc